(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Relevance of the work is determined by clarifying bioflavonoid — quercetin effect in treatment of age-related cataracts. Purpose. To study the effect of quercetin on the enzymatic system of the lens and humor in patients with age-related cataracts. Methods. Studies were conducted in 88patients with age-related cataracts before surgical treatment. Patients were divided into two groups: a control group — 43 patients with age-related cataracts who did not receive preoperative Lipoflavon, the main group — 45 patients with age-related cataracts treated preoperatively with Lipoflavon orally and quercetin. The determination of content of superoxide dismutase, catalase and glutathione peroxidase was made in the lens and humor. Results. Overall analysis of clinical studies shows a pronounced protective effect of bioflavonoid — quercetin on the enzymatic antioxidant system in the lens and humor in patients with age-related cataracts. Conclusions. Application of quercetin in patients with age-related cataracts before surgery has a strong activating effect on the activity of antioxidant enzymes of the lens. The most pronounced activation was observed under the influence of querce-tin in catalase. Under these conditions, humor of patients with age-related cata¬racts was noted to have a normalizing effect on the state of the studied bioflavonoid enzymes of catalase and glutathione peroxidase.